Metrik Reissner-Nordstr¨om dalam Teori Gravitasi Einstein: Canisius Bernard - Canisius Bernard Canisius Bernard (Jurnal Fisika dan Aplikasinya, 2017)
In this paper, we review that Reissner-Nordstr¨om metric is the solution of Einstein gravitational field equation. Reissner-Nordstr¨om solution describes spacetime outside a static spherically symmetric charged mass. To solve the field equation, we calculate all the non-zero components of Einstein tensor and energy-momentum tensor of the electromagnetic field of the charged object. One finds that the Reissner-Nordstr¨om metric is also a charged static black hole solution in Einstein-Maxwell theory.